Distribusi Salinitas dan Temperatur Permukaan Berdasarkan Angin dan Arus di Selat Madura - Muhamad Samodro Abdulrohiim Rohiim; Supriyatno Widagdo; Viv Djanat Prasita (Universitas Hang Tuah, 2022)
Salinity and Sea Surface Temperature (SST) are important parameters in oceanographic and climate studies. The value of salinity at sea level is caused by precipitation and evaporation of fresh water and is influenced by the entry of fresh water into sea waters. In addition, physical parameters such as wind, ocean currents, and rainfall can also affect horizontal salinity values. Several factors that affect SST are: depth, intensity of sunlight, precipitation and evaporation, as well as wind and air circulation. The purpose of this study was to analyze the effect of seasonal wind and current patterns on salinity and SST in the Madura Strait. The period studied was from 2010 to 2020 with the main parameters analyzed were salinity, SST, wind and currents as well as rainfall and river flows that emptied into the waters as supporting parameters. The results of this study showed that the minimum average salinity value occurred in the transition season at the beginning of the year with a value of 31.8 0/00 and the highest value of 32.77 0/00 occurred in the transition season at the end of the year. And for the lowest average SPL value occurred in the east monsoon season with a value of 28.38 oC and the highest SPL value of 30.17 oC which occurred in the transition season at the beginning of the year.